Super-hydrophilic strong sulfur-phobic bifunctional catalyst as well as preparation method and application of super-hydrophilic strong sulfur-phobic bifunctional catalyst
By synthesizing co-doped iron selenide electrode material with co-doped co-doped co-Fullow ferrose electrode material on NF substrate, the problems of slow oxygen evolution reaction and catalyst stability in traditional electrocatalytic technology are solved, and efficient hydrogen generation and catalyst self-cleaning effects are achieved.
Patent Information
- Application Number
- CN202411911149.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-24
AI Technical Summary
In traditional electrocatalytic water cracking hydrogen production technology, the slow kinetic properties of oxygen evolution reaction (OER) limit the economic benefits and wide application of the technology, and transition metal selenide catalysts face bubble interference, hydrophobicity and stability problems in practical applications.
The in-situ synthesis of co-doped co-doped iron selenide electrode material on a three-dimensional conductive NF substrate was achieved by two-step hydrothermal reduction method, and CoMo-Fe3Se4/NF composite material with super-hydrophilicity and strong sulfur-repellent properties was prepared.
It significantly improves the conductivity and electrocatalytic activity of the catalyst, improves the hydrogen bubble detachment and the self-cleaning effect of the catalyst, and improves the efficiency and stability of the HER and SOR reactions.
Smart Images

Figure BDA0005205693370000091 
Figure HDA0005205693380000011 
Figure HDA0005205693380000012
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalyst preparation, and specifically relates to a super-hydrophilic and strongly sulfur-repellent bifunctional catalyst and a preparation method and application thereof. Background Art
[0002] Electrocatalytic water splitting plays an indispensable role in promoting the goal of carbon neutrality. However, the slow kinetics of the traditional oxygen evolution reaction (OER) limit the economic benefits and widespread application of this technology. To this end, researchers have developed a series of new methods to couple electrooxidation reactions with hydrogen evolution reactions (HER). Such electrooxidation reactions, such as biomass oxidation, urea oxidation, and hydrazine oxidation, are not only thermodynamically more favorable and can reduce energy requirements, but also generate by-products with economic value. At the same time, hydrogen sulfide (H2S), as a harmful by-product in the process of petroleum refining and natural gas extraction, is usually absorbed and converted into sulfide in an alkaline environment. It is worth noting that H2S is a high-energy substance that is easily oxidized. Based on this feature, the ultra-low energy sulfide oxidation reaction (SOR) can be combined with the hydrogen evolution reaction (HER) to achieve efficient collection of hydrogen.
[0003] Finding high-performance bifunctional catalysts is one of the major challenges facing the current SOR||HER coupling system. Although noble metal catalysts show excellent electrocatalytic activity, their high cost greatly limits their wide application prospects. In contrast, transition metal selenides have become potential electrocatalysts in the HER and SOR reactions due to their unique layered structure, relatively narrow band gap, special morphology and low cost. However, there are still many obstacles in practical applications, including: (1) During the HER process, the large bubbles generated will interfere with the charge transfer and mass transfer between the solid-liquid interface, thereby causing the catalytic activity of selenides to gradually weaken; (2) Some catalyst surfaces show extremely strong hydrophobicity, with water contact angles far exceeding 90°. This feature may be the key factor for their low HER catalytic efficiency in alkaline environments. (3) Long-term and violent bubble impact may cause the catalyst to fall off, especially for powdered catalysts, which will significantly weaken the stability of the electrocatalyst.
[0004] Therefore, the overall performance of the catalyst can be significantly improved by adopting a variety of strategies to increase the density and conductivity of active sites. First, heteroatom doping, as an effective method to regulate the electronic structure, plays a vital role in enhancing the electrocatalytic performance. Although single-element doping can improve the activity of the catalyst to a certain extent, its room for improvement is relatively limited. In contrast, co-doping technology, especially bimetallic co-doping, can reconfigure the electronic structure through synergistic effects, which not only greatly improves the conductivity of the material, but also greatly enhances its inherent electrocatalytic activity. In addition, choosing conductive materials as substrates to synthesize catalysts is an extremely effective way to achieve efficient catalytic performance. Compared with traditional powdered catalysts, monolithic catalysts not only simplify the preparation process of the electrode, but also concentrate the active sites by increasing the loading amount, and at the same time, by eliminating the use of binders, more active sites can directly participate in the reaction. The uniform dispersion of the catalyst on the carrier helps to optimize the charge transfer efficiency, and the application of hydrophilic surface treatment technology can further improve the morphology and microstructure of the catalyst, ensuring that it is firmly attached to the substrate, thereby significantly improving the stability and electrocatalytic activity of the system. In summary, these two strategies can be used to directionally design catalysts and synthesize a bifunctional electrocatalyst with excellent electrocatalytic performance and good hydrophilicity. Summary of the invention
[0005] In order to effectively solve the above problems, the present invention adopts a two-step hydrothermal reduction method to successfully realize the in-situ synthesis of cobalt-molybdenum co-doped iron selenide electrode materials on NF substrates. This material not only has superhydrophilicity and excellent sulfur-repelling properties, but also reshapes the electronic structure of the material through the synergistic regulation strategy of bimetallic doping, thereby greatly improving its electrical conductivity and inherent electrocatalytic activity. Finally, we successfully prepared a transition metal selenide bifunctional catalyst with excellent catalytic activity.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] 1. A super-hydrophilic and strongly sulfur-repellent bifunctional catalyst, the structural unit of the catalyst includes a three-dimensional porous NF substrate and a bimetallic co-doped iron selenide active component in situ grown on the substrate; the bimetallic co-doped iron selenide catalyst is specifically CoMo-Fe3Se4 / NF;
[0008] Furthermore, CoMo-Fe3Se4 / NF was prepared by first synthesizing a layered hydroxide precursor, CoMoFe-LDF / NF, on NF and then converting it via a hydrothermal selenization process;
[0009] Furthermore, the loading amount of CoMo-Fe3Se4 on NF is 20-30 mg cm -2 ;
[0010] 2. A method for preparing a super-hydrophilic and strongly sulfur-repellent bifunctional catalyst, comprising:
[0011] S1. Synthesis of CoMoFe-LDF / NF precursor: dissolve iron salt, cobalt salt, molybdenum source, urea and ammonium fluoride in deionized water, transfer the mixed solution to a polytetrafluoroethylene container after stirring, add pretreated NF, and perform hydrothermal reaction at 180-230°C for 5.5-8.5h. After the reaction is completed, cool naturally to room temperature, rinse the catalyst with deionized water and anhydrous ethanol for 2-3 times respectively, and obtain CoMoFe-LDF / NF precursor;
[0012] S2, synthesis of CoMo-Fe3Se4 / NF: ultrasonically dissolve the reducing agent in deionized water, add the selenium source thereto, stir to fully dissolve it, and obtain a mixed solution. Transfer the uniform mixed solution to a polytetrafluoroethylene container, add the CoMoFe-LDF / NF precursor synthesized in S1 thereto, and perform hydrothermal reaction at 90-130°C for 0.5-4.5h. After the reaction is completed, naturally cool to room temperature, rinse the catalyst with deionized water and anhydrous ethanol for 2-3 times, respectively, to obtain CoMo-Fe3Se4 / NF;
[0013] In the step S1, the NF pretreatment step is: ultrasonic treatment in a 3M HCl solution for 20 to 40 minutes, followed by rinsing with deionized water and anhydrous ethanol three times each, and finally, drying the treated sample in a vacuum drying oven at 60°C for subsequent use;
[0014] The molar ratio of molybdenum, cobalt and iron in molybdenum salt, cobalt salt and iron salt is 2:4:1-6:4:1; more preferably, the molar ratio of iron, cobalt and molybdenum is 1:4:4; the molar ratio of urea and ammonium fluoride is 1:6-1:12; the molar ratio of iron and urea is 1:3;
[0015] In step S1, the iron salt is one or more of Fe(NO3)2·9H2O, Fe2(SO4)3·9H2O, and FeCl3·6H2O; the cobalt salt is one or more of Co(CH3COO)2·4H2O, Co(NO3)2·6H2O, and CoCl2·6H2O; the molybdenum source is (NH4)6Mo7O 24 ·4H2O, Na2MoO4·2H2O or more;
[0016] In the step S2, the molar ratio of the reducing agent to the selenium source is 1:1 to 4.5:1; the molar ratio of the iron element to the selenium source is 1:2.7 to 3.0;
[0017] In the step S2, the selenium source is one or more of Se, SeO2, and Na2SeO3; the reducing agent is one or more of NaBH4, hydrazine hydrate, ammonia water, and urea.
[0018] The length of NF is 1.0 cm, the width is 1.5 cm, and the thickness is 0.1 cm;
[0019] Another object of the present invention is to overcome the limitations of the prior art and propose an application of a super-hydrophilic and strongly sulfur-phobic bifunctional catalyst in SOR and HER.
[0020] Beneficial effects of the present invention:
[0021] (1) The present invention synthesized a CoMo-Fe3Se4 / NF composite material with super hydrophilicity and strong sulfur-repelling property on a three-dimensional conductive NF substrate. During the HER process, the continuous and strong bubbles generated are easy to adhere to the catalyst surface, which not only hinders the charge transfer and material transfer between the solid-liquid interface, but also may block the active sites and affect the catalytic efficiency. However, thanks to the excellent hydrophilicity of CoMo-Fe3Se4 / NF, it can effectively improve the wettability of the electrolyte to the electrode, making it easier for hydrogen bubbles to detach and escape from the electrode surface, thereby ensuring a sufficient supply of active sites and significantly improving the efficiency and of the HER reaction; at the same time, the present invention also has sulfur-repelling properties, which can effectively prevent sulfur from adhering to the catalyst surface, thereby achieving the self-cleaning and anti-passivation effect of the electrocatalyst.
[0022] (2) The present invention synthesizes a layered hydroxide precursor and successfully prepares the CoMo-Fe3Se4 / NF composite material by hydrothermal reduction. This special structural design can evenly disperse the active components, making the active sites more easily exposed, which is conducive to the full contact between the reaction intermediates and the active sites, thereby improving the electrocatalytic efficiency.
[0023] (3) The present invention increases the active sites of the catalyst by co-doping Co and Mo, produces a strong synergistic effect, successfully adjusts the electronic configuration of Fe3Se4, and enhances its intrinsic activity, thereby improving the electrocatalytic performance of HER and SOR reactions. Therefore, Co and Mo co-doping has opened up a promising method for the development of nickel-based selenide electrocatalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the XRD diagram of CoMo-Fe3Se4 / NF-1 synthesized in Example 1 of the present invention.
[0025] Figure 2 is the water contact angle of the CoMo-Fe3Se4 / NF-1 catalyst in Example 1 of the present invention ( Figure 2 (a)) and sulfur contact angle ( Figure 2 (b))Picture.
[0026] Figure 3 The linear sweep voltammetric curves of the catalysts synthesized in the examples and comparative examples of the present invention are shown in FIG. Figure 3 (a) Linear sweep voltammetric curves of HER of CoMo-Fe3Se4 / NF-1, CoMo-Fe3Se4 / NF-2, CoMo-Fe3Se4 / NF-3, Co-Fe3Se4 / NF, and Fe3Se4 / NF; Figure 3 (b) Linear sweep voltammetric curves of SOR of CoMo-Fe3Se4 / NF-1, CoMo-Fe3Se4 / NF-2, CoMo-Fe3Se4 / NF-3, Co-Fe3Se4 / NF, and Fe3Se4 / NF.
[0027] Figure 4 This is a two-electrode linear sweep voltammetry curve of the SOR||HER coupling system catalyst electrode in Example 4 of the present invention. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical scheme and beneficial technical effects of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the embodiments described in this specification are only for explaining the present invention, not for limiting the present invention, and the parameters, proportions, etc. of the embodiments can be selected according to local conditions without substantial effect on the results.
[0029] Example 1
[0030] CoMo-Fe3Se4 / NF-1 was prepared according to the following steps:
[0031] (1) Pretreatment of NF matrix: The cut NF (length: 1.0 cm, width: 1.5 cm, thickness: 0.1 cm) was immersed in 3M hydrochloric acid solution and ultrasonicated for 30 min to remove the oxide film on the surface. The NF was then rinsed three times with deionized water and anhydrous ethanol and placed in a vacuum drying oven at 60°C for later use.
[0032] (2) Synthesis of CoMoFe-LDF / NF precursor: Dissolve 1mmol Fe(NO3)2·9H2O, 4mmol Co(NO3)2·6H2O, and 4mmol Na2MoO4·2H2O in 30.00mL deionized water and stir for 30min to obtain a uniform solution. Then add 182mg urea and 977.6mg ammonium fluoride. After stirring evenly, transfer the mixed solution to a polytetrafluoroethylene container and add pretreated NF. Perform hydrothermal reaction at 200℃ for 6h. After the reaction is completed, cool naturally to room temperature. Rinse the catalyst with deionized water and anhydrous ethanol for 2 to 3 times, respectively, to obtain CoMoFe-LDF / NF precursor.
[0033] (3) Synthesis of CoMo-Fe3Se4 / NF-1: 264 mg of NaBH4 was ultrasonically dissolved in 35.00 mL of deionized water, and 236.22 mg of selenium powder was added thereto. The mixture was stirred for 30 min to fully dissolve. The uniform mixed solution was transferred to a polytetrafluoroethylene container, and the CoMoFe-LDF / NF precursor synthesized in S1 was added thereto. The mixture was hydrothermally reacted at 120°C for 2 h. After the reaction was completed, it was naturally cooled to room temperature. The catalyst was rinsed 2 to 3 times with deionized water and anhydrous ethanol, respectively, to obtain CoMo-Fe3Se4 / NF-1.
[0034] Description: The structure of CoMo-Fe3Se4 / NF-1 in Example 1 was analyzed by X-ray diffractometer. Figure 1 As shown, the XRD spectrum corresponds to the standard card, which fully proves the successful preparation of CoMo-Fe3Se4 / NF-1. At the same time, the water contact angle of CoMo-Fe3Se4 / NF-1 was tested ( Figure 2 (a)), the water contact angle of CoMo-Fe3Se4 / NF-1 is close to 0°, and the water droplets are absorbed as soon as they touch the catalyst surface. CoMo-Fe3Se4 / NF-1 exhibits obvious superhydrophilicity, which is conducive to the wetting of the catalyst by the electrolyte, making it easier for hydrogen bubbles to detach and escape from the electrode surface, ensuring sufficient supply of active sites, thereby enhancing HER activity.
[0035] The test method of sulfur contact angle is as follows: First, melt sulfur at 120°C. At the same time, fix the sample to be tested on the workbench and make sure it is in a horizontal state, then drip sulfur, slowly adjust the sulfur to form a droplet on the needle, then raise the height of the workbench, slowly move the sample surface and the sulfur droplet to gently contact, and the sulfur droplet gently falls on the sample surface. The angle measured at this time is the sulfur contact angle. The test standard is: a sulfur contact angle greater than 90° indicates sulfur repellency, and less than 90° indicates sulfur affinity. Figure 2(b) is the sulfur contact angle image of CoMo-Fe3Se4 / NF-1 obtained by melting sulfur at 120°C. It can be seen from the figure that the sulfur contact angle of CoMo-Fe3Se4 / NF-1 is 119°, showing strong sulfur-repelling properties, which is beneficial for the catalyst to maintain long-term stability during the SOR process.
[0036] Comparative Example 1
[0037] Co-Fe3Se4 / NF was prepared according to the following steps:
[0038] Preparation of Co-Fe3Se4 / NF catalyst:
[0039] (1) The pretreatment of the NF substrate was the same as in Example 1;
[0040] (2) Synthesis of CoFe-LDF / NF precursor: Dissolve 1mmol Fe(NO3)2·9H2O and 4mmol Co(NO3)2·6H2O in 30.00mL deionized water and stir for 30min to obtain a uniform solution. Then add 182mg urea and 977.6mg ammonium fluoride. After stirring evenly, transfer the mixed solution to a polytetrafluoroethylene container and add the treated NF. Perform hydrothermal reaction at 200℃ for 6h. After the reaction is completed, cool naturally to room temperature. Rinse the catalyst with deionized water and anhydrous ethanol for 2 to 3 times respectively to obtain CoFe-LDF / NF precursor.
[0041] (3) Synthesis of Co-Fe3Se4 / NF: 264 mg of NaBH4 was ultrasonically dissolved in 35.00 mL of deionized water, and 236.22 mg of selenium powder was added thereto. The mixture was stirred for 30 min to fully dissolve. The uniform mixed solution was transferred to a polytetrafluoroethylene container, and the CoFe-LDF / NF precursor synthesized in S1 was added thereto. The mixture was hydrothermally reacted at 120 °C for 2 h. After the reaction was completed, it was naturally cooled to room temperature. The catalyst was rinsed 2 to 3 times with deionized water and anhydrous ethanol, respectively, to obtain Co-Fe3Se4 / NF.
[0042] Comparative Example 2
[0043] The Fe3Se4 / NF catalyst was prepared according to the following steps:
[0044] (1) The pretreatment of the NF substrate was the same as in Example 1;
[0045] (2) Synthesis of Fe-LDF / NF precursor: Dissolve 1 mmol Fe(NO3)2·9H2O in 30.00 mL deionized water and stir for 30 min to obtain a uniform solution. Then add 182 mg urea and 977.6 mg ammonium fluoride. After stirring evenly, transfer the mixed solution to a polytetrafluoroethylene container and add the treated NF. Perform a hydrothermal reaction at 200°C for 6 h. After the reaction is completed, cool the mixture to room temperature naturally. Rinse the catalyst with deionized water and anhydrous ethanol for 2 to 3 times, respectively, to obtain the Fe-LDF / NF precursor.
[0046] (2) Synthesis of Fe3Se4 / NF: 264 mg of NaBH4 was ultrasonically dissolved in 35.00 mL of deionized water, and 236.22 mg of selenium powder was added thereto. The mixture was stirred for 30 min to fully dissolve. The uniform mixed solution was transferred to a polytetrafluoroethylene container, and the Fe-LDF / NF precursor synthesized in S1 was added thereto. The mixture was hydrothermally reacted at 120 °C for 2 h. After the reaction was completed, it was naturally cooled to room temperature. The catalyst was rinsed 2 to 3 times with deionized water and anhydrous ethanol, respectively, to obtain Fe3Se4 / NF.
[0047] Comparative Example 3
[0048] Mo-Fe3Se4 / NF was prepared according to the following steps:
[0049] (1) The pretreatment of the NF substrate was the same as in Example 1.
[0050] (2) Synthesis of MoFe-LDF / NF precursor: Dissolve 1mmol Fe(NO3)2·9H2O and 4mmol Na2MoO4·2H2O in 30.00mL deionized water and stir for 30min to obtain a uniform solution. Then add 182mg urea and 977.6mg ammonium fluoride. After stirring evenly, transfer the mixed solution to a polytetrafluoroethylene container and add the treated NF. Perform hydrothermal reaction at 200℃ for 6h. After the reaction is completed, cool naturally to room temperature. Rinse the catalyst with deionized water and anhydrous ethanol for 2 to 3 times respectively to obtain MoFe-LDF / NF precursor.
[0051] (3) Synthesis of Mo-Fe3Se4 / NF: 264 mg of NaBH4 was ultrasonically dissolved in 35.00 mL of deionized water, and 236.22 mg of selenium powder was added thereto. The mixture was stirred for 30 min to fully dissolve. The uniform mixed solution was transferred to a polytetrafluoroethylene container, and 3 pieces of MoFe-LDF / NF precursor synthesized in S1 were added thereto. The mixture was hydrothermally reacted at 120°C for 2 h. After the reaction was completed, it was naturally cooled to room temperature. The catalyst was rinsed 2 to 3 times with deionized water and anhydrous ethanol, respectively, to obtain Mo-Fe3Se4 / NF.
[0052] Example 2
[0053] Compared with Example 1, Example 2 differs in that: step (3) is subjected to hydrothermal reaction at 120° C. for 1 h, and other operations are the same as those in Example 1.
[0054] CoMo-Fe3Se4 / NF-2 was prepared according to the following steps:
[0055] (1) Pretreatment of NF matrix: The cut NF was immersed in 3M hydrochloric acid solution and ultrasonicated for 30 min to remove the oxide film on the surface. The NF was then rinsed three times with deionized water and anhydrous ethanol and placed in a vacuum drying oven at 60°C for later use.
[0056] (2) Synthesis of CoMoFe-LDF / NF precursor: Dissolve 1mmol Fe(NO3)2·9H2O, 4mmol Co(NO3)2·6H2O, and 4mmol Na2MoO4·2H2O in 30.00mL deionized water and stir for 30min to obtain a uniform solution. Then add 182mg urea and 977.6mg ammonium fluoride. After stirring evenly, transfer the mixed solution to a polytetrafluoroethylene container and add the treated NF. Incubate the mixture at 200℃ for 6h for hydrothermal reaction. After the reaction is completed, cool the mixture to room temperature naturally. Rinse the catalyst with deionized water and anhydrous ethanol for 2 to 3 times to obtain CoMoFe-LDF / NF precursor.
[0057] (3) Synthesis of CoMo-Fe3Se4 / NF-2: 264 mg of NaBH4 was ultrasonically dissolved in 35.00 mL of deionized water, and 236.22 mg of selenium powder was added thereto. The mixture was stirred for 30 min to fully dissolve. The uniform mixed solution was transferred to a polytetrafluoroethylene container, and the CoMoFe-LDF / NF precursor synthesized in S1 was added thereto. The mixture was hydrothermally reacted at 120°C for 1 h. After the reaction was completed, it was naturally cooled to room temperature. The catalyst was rinsed 2 to 3 times with deionized water and anhydrous ethanol, respectively, to obtain CoMo-Fe3Se4 / NF-2.
[0058] Example 3
[0059] Compared with Example 1, Example 3 differs in that: step (3) is subjected to hydrothermal reaction at 120° C. for 3 h, and other operations are the same as those in Example 1.
[0060] CoMo-Fe3Se4 / NF-3 was prepared according to the following steps:
[0061] (1) Pretreatment of NF matrix: The cut NF was immersed in 3M hydrochloric acid solution and ultrasonicated for 30 min to remove the oxide film on the surface. The NF was then rinsed three times with deionized water and anhydrous ethanol and placed in a vacuum drying oven at 60°C for later use.
[0062] (2) Synthesis of CoMoFe-LDF / NF precursor: Dissolve 1mmol Fe(NO3)2·9H2O, 4mmol Co(NO3)2·6H2O, and 4mmol Na2MoO4·2H2O in 30.00mL deionized water and stir for 30min to obtain a uniform solution. Then add 182mg urea and 977.6mg ammonium fluoride. After stirring evenly, transfer the mixed solution to a polytetrafluoroethylene container and add the treated NF. Incubate the mixture at 200℃ for 6h for hydrothermal reaction. After the reaction is completed, cool the mixture to room temperature naturally. Rinse the catalyst with deionized water and anhydrous ethanol for 2 to 3 times to obtain CoMoFe-LDF / NF precursor.
[0063] (3) Synthesis of CoMo-Fe3Se4 / NF-3: 264 mg of NaBH4 was ultrasonically dissolved in 35.00 mL of deionized water, and 236.22 mg of selenium powder was added thereto. The mixture was stirred for 30 min to fully dissolve. The uniform mixed solution was transferred to a polytetrafluoroethylene container, and the CoMoFe-LDF / NF precursor synthesized in S1 was added thereto. The mixture was hydrothermally reacted at 120°C for 3 h. After the reaction was completed, it was naturally cooled to room temperature. The catalyst was rinsed 2 to 3 times with deionized water and anhydrous ethanol, respectively, to obtain CoMo-Fe3Se4 / NF-3.
[0064] Example 4
[0065] Compared with Example 1, Example 4 differs in that 4 mmol Co(NO3)2·6H2O is replaced by 3 mmol Na2MoO4·2H2O, and the other operations are the same as those in Example 1.
[0066] CoMo-Fe3Se4 / NF-4 was prepared according to the following steps:
[0067] (1) Pretreatment of NF matrix: The cut NF was immersed in 3M hydrochloric acid solution and ultrasonicated for 30 min to remove the oxide film on the surface. The NF was then rinsed three times with deionized water and anhydrous ethanol and placed in a vacuum drying oven at 60°C for later use.
[0068] (2) Synthesis of CoMoFe-LDF / NF precursor: Dissolve 1mmol Fe(NO3)2·9H2O, 4mmol Co(NO3)2·6H2O, and 3mmol Na2MoO4·2H2O in 30.00mL deionized water and stir for 30min to obtain a uniform solution. Then add 182mg urea and 977.6mg ammonium fluoride. After stirring evenly, transfer the mixed solution to a polytetrafluoroethylene container and add the treated NF. Incubate the mixture at 200℃ for 6h for hydrothermal reaction. After the reaction is completed, cool the mixture to room temperature naturally. Rinse the catalyst with deionized water and anhydrous ethanol for 2 to 3 times to obtain the CoMoFe-LDF / NF precursor.
[0069] (3) Synthesis of CoMo-Fe3Se4 / NF-4: 264 mg of NaBH4 was ultrasonically dissolved in 35.00 mL of deionized water, and 236.22 mg of selenium powder was added thereto. The mixture was stirred for 30 min to fully dissolve. The uniform mixed solution was transferred to a polytetrafluoroethylene container, and the CoMoFe-LDF / NF precursor synthesized in S1 was added thereto. The mixture was hydrothermally reacted at 120°C for 2 h. After the reaction was completed, it was naturally cooled to room temperature. The catalyst was rinsed 2 to 3 times with deionized water and anhydrous ethanol, respectively, to obtain CoMo-Fe3Se4 / NF-4.
[0070] Example 5
[0071] Compared with Example 1, Example 5 differs in that 4 mmol Co(NO3)2·6H2O is replaced by 5 mmol Na2MoO4·2H2O, and the other operations are the same as those in Example 1.
[0072] CoMo-Fe3Se4 / NF-5 was prepared according to the following steps:
[0073] (1) Pretreatment of NF matrix: The cut NF was immersed in 3M hydrochloric acid solution and ultrasonicated for 30 min to remove the oxide film on the surface. The NF was then rinsed three times with deionized water and anhydrous ethanol and placed in a vacuum drying oven at 60°C for later use.
[0074] (2) Synthesis of CoMoFe-LDF / NF precursor: Dissolve 1mmol Fe(NO3)2·9H2O, 4mmol Co(NO3)2·6H2O, and 5mmol Na2MoO4·2H2O in 30.00mL deionized water and stir for 30min to obtain a uniform solution. Then add 182mg urea and 977.6mg ammonium fluoride. After stirring evenly, transfer the mixed solution to a polytetrafluoroethylene container and add the treated NF. Perform hydrothermal reaction at 200℃ for 6h. After the reaction is completed, cool naturally to room temperature. Rinse the catalyst with deionized water and anhydrous ethanol for 2 to 3 times, respectively, to obtain CoMoFe-LDF / NF precursor.
[0075] (3) Synthesis of CoMo-Fe3Se4 / NF-5: 264 mg of NaBH4 was ultrasonically dissolved in 35.00 mL of deionized water, and 236.22 mg of selenium powder was added thereto. The mixture was stirred for 30 min to fully dissolve. The uniform mixed solution was transferred to a polytetrafluoroethylene container, and the CoMoFe-LDF / NF precursor synthesized in S1 was added thereto. The mixture was hydrothermally reacted at 120°C for 2 h. After the reaction was completed, it was naturally cooled to room temperature. The catalyst was rinsed 2 to 3 times with deionized water and anhydrous ethanol, respectively, to obtain CoMo-Fe3Se4 / NF-5.
[0076] Description: Evaluation of HER and SOR performance of catalysts: Linear sweep voltammetry is used to evaluate the performance of the catalyst. Using a three-electrode system, the hydrogen evolution reaction (HER) activity is tested in a 1.0M NaOH solution, and the SOR activity is tested in a mixed solution containing NaOH and Na2S (a mixed solution formed by dissolving 1 mol NaOH and 1 mol Na2S solids in 1L deionized water). At the same time, a platinum electrode is used as the counter electrode, Ag / AgCl is used as the reference electrode, and the catalyst synthesized in the embodiment and the comparative example is used as the working electrode. The linear sweep voltammetry curve test of HER is carried out in the voltage range of 1.0-1.6V (relative to Ag / AgCl) at a scan rate of 5mV / s, and the linear sweep voltammetry curve test of SOR is carried out in the voltage range of -0.2 to -1.0V (relative to Ag / AgCl) at a scan rate of 5mV / s. The results are shown as follows. Figure 2 (ab) and shown in Table 1.
[0077] Table 1 Different catalysts at 100 mA·cm -2 Comparison of overpotentials of SOR and HER at different current densities
[0078]
[0079] As shown in Table 1, the single-phase Fe3Se4 / NF exhibits poor electrocatalytic activity. After the introduction of a single Co element, Co-Fe3Se4 / NF exhibits better activity compared with it. After the introduction of bimetallic, CoMo-Fe3Se4 / NF-1 exhibits the best catalytic activity. This is because single doping still has certain limitations. Co-doping can produce a strong synergistic effect by adjusting the electronic structure, thereby improving the electrocatalytic performance. At the same time, the hydrothermal reaction time also has a great influence on the performance of the catalyst. The results show that the CoMo-Fe3Se4 / NF-1 synthesized by the second step hydrothermal reaction 2h exhibits the best electrocatalytic activity. Finally, the content of Mo will also affect the performance of the catalyst. The results show that when the amount of Mo is 4mmol, the synthesized CoMo-Fe3Se4 / NF-1 exhibits the best electrocatalytic activity. The present invention successfully adjusts the electronic configuration of Fe3Se4 through Co and Mo elements and enhances its intrinsic activity, opening up a promising method for the development of iron-based selenide electrocatalysts.
[0080] Example 6
[0081] (1) Construction of HER||SOR coupling system performance: CoMo-Fe3Se4 / NF-1 was used as the cathode electrode and anode electrode of the H-type electrolytic cell, respectively, to construct a two-electrode system for testing. The cathode electrolyte was a 1.0 M NaOH aqueous solution, and the anode electrolyte was a mixed solution of 1 mol NaOH and 1 mol Na2S solid dissolved in 1 L deionized water. The diaphragm was a cationic membrane (DuPont, Nafion 117), which was Na + The transport of ions provides channels to maintain ionic charge balance and divide the anode / cathode regions. Linear sweep voltammetry tests were performed at a voltage of 0-2.5V, and the test results were compensated with 90% infrared.
[0082] (2) Performance of HER||OER coupling system: The test was conducted on a CHI660E electrochemical workstation, using the CoMo-Fe3Se4 / NF-1 electrode material obtained in Example 1 as the working electrode, the platinum electrode as the counter electrode, and the cathode and anode electrolytes were both 1.00 M NaOH aqueous solution. The HER||OER coupling system was tested at 5 mV·s in the range of 1.2-2.0 V (relative to Ag / AgCl). -1 The linear sweep voltammetry (LSV) curve was tested at a scan rate of , and 90% impedance compensation was adopted to obtain the final LSV curve.
[0083] illustrate: Figure 4 The LSV comparison diagram of SOR||HER and OER||HER coupling system under two-electrode system shows that at 100 mA cm -2At a current density of , the SOR||HER coupling system only requires a voltage of 0.676 V to reach the corresponding current density, while the OER||HER system requires a voltage of 1.719 V. It can be seen that the energy consumption of hydrogen production in the SOR||HER system is much lower than the energy consumption required for hydrogen production by water electrolysis.
[0084] In summary, the CoMo-Fe3Se4 / NF-1 bifunctional catalyst synthesized in the present invention has excellent HER and SOR performances, and can successfully drive the SOR||HER coupling system, which makes the present invention show great potential and development prospects in the application fields of hydrogen production and sulfur removal.
[0085] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A super-hydrophilic and strong sulfur-repellent bifunctional catalyst, characterized in that: The catalyst comprises a three-dimensional porous NF substrate and a bimetallic co-doped iron selenide active component in-situ grown on the NF substrate, and the catalyst is specifically CoMo-Fe3Se4 / NF.
2. The method for preparing the super hydrophilic and strong sulfur-repellent bifunctional catalyst according to claim 1, characterized in that: The layered hydroxide precursor CoMoFe-LDF / NF was first synthesized on NF and then converted through a hydrothermal selenization process to obtain CoMo-Fe3Se4 / NF.
3. The method for preparing a super hydrophilic and highly sulfur-repellent bifunctional catalyst as claimed in claim 2, characterized in that: S1. Synthesis of CoMoFe-LDF / NF precursor: dissolve iron salt, cobalt salt, molybdenum source, urea and ammonium fluoride in water, transfer the mixed solution to a polytetrafluoroethylene container after stirring, add pretreated NF, and perform hydrothermal reaction at 180-230°C for 5.5-8.5h. After the reaction is completed, cool and rinse to obtain CoMoFe-LDF / NF precursor; S2. Synthesis of CoMo-Fe3Se4 / NF: ultrasonically dissolve the reducing agent in deionized water, add the selenium source and stir to fully dissolve it to obtain a mixed solution. Transfer the uniform mixed solution to a polytetrafluoroethylene container, add the CoMoFe-LDF / NF precursor synthesized in S1, and conduct hydrothermal reaction at 90-130°C for 0.5-4.5h. After the reaction is completed, cool to room temperature and wash to obtain CoMo-Fe3Se4 / NF.
4. The method for preparing the super hydrophilic and strong sulfur-repellent bifunctional catalyst according to claim 3, characterized in that: In step S1, the NF pretreatment step is: subjecting the NF substrate to ultrasonic treatment in an HCl solution for 20 to 40 minutes, followed by rinsing with deionized water and anhydrous ethanol, respectively, and finally, vacuum drying the treated sample.
5. The method for preparing the super hydrophilic and strong sulfur-repellent bifunctional catalyst as claimed in claim 3, characterized in that: The molar ratio of molybdenum, cobalt and iron in the molybdenum salt, cobalt salt and iron salt is 2:4:1-6:4:1; the molar ratio of urea and ammonium fluoride is 1:6-1:12; and the molar ratio of iron and urea is 1:
3.
6. The method for preparing the super hydrophilic and strong sulfur-repellent bifunctional catalyst according to claim 4, characterized in that: The molar ratio of iron, cobalt and molybdenum is 1:4:
4.
7. The method for preparing the super hydrophilic and strong sulfur-repellent bifunctional catalyst according to claim 3, characterized in that: In step S2, the molar ratio of the reducing agent to the selenium source is 1:1 to 4.5:1; the molar ratio of the iron element to the selenium source is 1:2.7 to 3.
0.
8. The method for preparing the super hydrophilic and strong sulfur-repellent bifunctional catalyst according to claim 3, characterized in that: The iron salt is one or more of Fe(NO3)2·9H2O, Fe2(SO4)3·9H2O, and FeCl3·6H2O; the cobalt salt is one or more of Co(CH3COO)2·4H2O, Co(NO3)2·6H2O, and CoCl2·6H2O; the molybdenum source is (NH4)6Mo7O 24 ·4H2O, Na2MoO4·2H2O or more thereof.
9. The method for preparing the super hydrophilic and strong sulfur-repellent bifunctional catalyst as claimed in claim 3, characterized in that: The selenium source is one or more of Se, SeO2, and Na2SeO3; the reducing agent is one or more of NaBH4, hydrazine hydrate, ammonia water, and urea.
10. Use of a super-hydrophilic and strong sulfur-repellent bifunctional catalyst prepared by the method according to any one of claims 2 to 9, characterized in that: Application of superhydrophilic and strongly sulfur-phobic bifunctional catalysts in electrocatalytic hydrogen evolution reaction and / or electrocatalytic sulfur ion oxidation reaction.
Citation Information
Patent Citations
Preparation method of pH eurytopic catalyst based on molybdenum-tungsten-based layered material, and application in water electrolysis hydrogen evolution reaction
CN112058282A
Multi-metal non-oxide electrocatalyst as well as preparation method and application thereof
CN113151854A
CoSe nanosheet electrocatalyst with cation vacancies as well as preparation method and application of CoSe nanosheet electrocatalyst
CN116516392A
Phosphorus-doped cobalt molybdate HER / SOR bifunctional catalyst, preparation method and application
CN117845256A
Cited By
Preparation method of nano needle tip array material for hydrogen production through electro-catalysis of hydrogen sulfide desulfurization
CN120291115A